ChemInform Abstract: Solid Solution Series Between CdIn2Te4 and AgInTe2 Investigated by Resonant X‐Ray Scattering. Issue 8 (February 2015) - Welzmiller, Simon; Hennersdorf, Felix; Fitch, Andy; Oeckler, Oliver
Abstract CdIn2Te4 (I) and AgInTe2 are prepared by melting stoichiometric amounts of the elements (silica ampoules, 1.